Humanity, Future Generations and Bioethics - Κουκουζέλης (Kostas Ν. Koukouzelis), Κώστας Ν. (Bioethica, 2016)
The moral status of future persons and future generations is one of the pertinent issues under discussion in bioethics and in particular environmental bioethics. There is, indeed, a vast skepticism on whether future generations have rights or whether we have duties towards them and of what kind. However, the main question, which the present essay puts forward, comes at a prior point. Do we have an interest in whether future generations will exist after all or whether humanity will continue to exist and what kind of interest is this? It is argued that we are in a sense dependent on future generations’ existence in a way we are not dependent on the continuation of our individual lives. This is because humanity’s existence into the future makes us value certain things and practices in our lives now, indeed it conditions valuing. After evaluating three objections to the aforementioned argument, I argue that our interest in the existence of future generations is something crucial for how human practical rationality and action works, it has an egalitarian nature, but does not involve future generations’ welfare. It finally stems from practical rationality itself.